(untitled) (Oshada, 2025)
Background: The rapid development of mobile technologies has enabled health promotion activities to be delivered more rapidly, repeatedly, and responsively, creating new opportunities to influence clean and healthy living behavior (CHLB) across diverse community settings. Method: This study employed a narrative review by synthesizing academic literature published over the last ten years that examined the implementation of mobile health campaigns and their influence on CHLB. Results: The findings indicate that mobile health campaigns delivered through multiple platforms, including WhatsApp, SMS, Instagram, Facebook, mobile health applications, and educational videos, contribute to improvements in CHLB knowledge, attitudes, and practices. Multiplatform approaches were found to be more effective than single-platform campaigns due to complementary features such as scheduled reminders, visual demonstrations, and digitally mediated interpersonal communication that reinforces trust in health information. Conclusion: Sustainable improvements in CHLB require not only increased health knowledge but also ongoing digital social support and behavioral reinforcement through continuous messaging. Strengthening mobile health campaigns through culturally relevant content, sustained communication, and active community participation is essential for long-term CHLB adoption.